Intercept probability analysis in DF time switching full-duplex relaying network with impact of Co-channel interference at the eavesdropper - Pham Minh Nam; Phu Tran Tin; Minh Tran (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
In this research, we propose and investigate intercept probability analysis in DF time switching relaying full-duplex with impact of Co-channel interference at the eavesdropper. In the beginning stage, we present the DF time switching relaying full-duplex with the Impact of Co-channel interference at the eavesdropper. Furthermore, the closed-form expression of the intercept probability (IP) is analyzed and derived in connection with the primary system parameters. Finally, the Monte Carlo simulation is performed for verifying the correctness of the analytical section. From the research results, a novel solution and some recommendations can be proposed for the communication network in the near future.